2015
DOI: 10.1002/eco.1668
|View full text |Cite
|
Sign up to set email alerts
|

Optimal vegetation cover in the Horqin Sands, China

Abstract: Vegetation cover is an important index describing vegetation distribution, which is widely used to study vegetation dynamics. Eagleson presented an optimal vegetation cover hypothesis by the tradeoff of water supply and water demand based on strict mathematical and physical derivation. According to Eagleson's ecohydrological optimality, the positive correlation curve between canopy conductance and vegetation cover is obtained based on water demand; the negative correlation curve between canopy conductance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…M * increases with the increase of leaf angle and decrease of stem fraction and LAI. Mo et al (2015) studied the relationship between vegetation properties and optimal canopy cover in Horqin Sand, China, and reached the same conclusion. In the grassland area, the water demand curve is more sensitive to the variation of h s / h compared to β. M * decreases by 0.037 as h s / h increases by 0.10.…”
Section: Sensitivity Of M * To Vegetation Propertiesmentioning
confidence: 65%
See 2 more Smart Citations
“…M * increases with the increase of leaf angle and decrease of stem fraction and LAI. Mo et al (2015) studied the relationship between vegetation properties and optimal canopy cover in Horqin Sand, China, and reached the same conclusion. In the grassland area, the water demand curve is more sensitive to the variation of h s / h compared to β. M * decreases by 0.037 as h s / h increases by 0.10.…”
Section: Sensitivity Of M * To Vegetation Propertiesmentioning
confidence: 65%
“…The optimality theory provides a new way to explore the quantitative relationship between vegetation and climate factors. Despite the fact that Eagleson's work is regarded as the basis for ecohydrology and is of great importance (Hatton et al, 1997;Kerkhoff et al, 2004), limited studies have been conducted using the theory in practice (Shao et al, 2011;Mo et al, 2015), which is partly due to the limitation of longterm temporal scale, partly due to the difficulty to measure vegetation characteristics. In Eagleson's ecohydrological optimality theory, the optimal canopy cover (M * ) is determined by the trade-off between water supply depending on water balance and water demand depending on canopy transpiration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mongolica in response to density, and found a reasonable density of approximately 2100 stems per hectare at an age of approximately 20 years. Mo et al [ 38 ] applied Eagleson’s ecohydrological optimality theory to determine the appropriate VC in vegetation restoration practice. These authors reported that the suitable VC (including grasslands/savanna, croplands and forests) is 0.318 in the Horqin sands.…”
Section: Introductionmentioning
confidence: 99%
“…Their research shows that the most effective use of humus mass stored in disturbed territories in combination with the natural regeneration of woody plants is the most effective use of sand reclamation [12,13]. However, the lack of humus or its ab sence, against the backdrop of unsatisfactory water regime of the sands, encourage scientists to look for methods for assess ing the risks associated with their ecological restoration [14], which provide for comprehensive studies, in particular, such as ecohydrological optimization with attraction remote sensing [15], elaboration of methods of moisture retention and water conservation in the recultivation layer of sands [3,16] and ap National University of Life and Environmental Sciences of Ukraine, Kyiv, Ukraine, email: fmbrovko@ukr.net https://doi.org/10.33271/nvngu/20201/111 plication of biocementation for cell surface by halotolerant bacteria [17], as well as identification of wood species that can successfully cultivate under such growth conditions [18]. These studies open up great opportunities to improve the edaphic conditions of the reclamation layer of sands provided they are forested.…”
mentioning
confidence: 99%